(untitled) (Experimental biology, 2023)
The article provides data on the biology and morphology of the Siberian minnow Gobio cynocephalus. Minnows (Gobio) belong to one of the most widespread freshwater fish species in Eurasia. This genus is characterized by great morphological variability. Currently, for the borders of the Republic of Kazakhstan, A.L.Martynova and E.D.Vasilyeva (2021) indicate 3 types of minnows. The Volga minnow Gobio volgensis Vasil’eva, Mendel, Vasil’ev, Lusk, Lusková, 2008 inhabits the Volga and Ural rivers. Turkestan minnow G.lepidolaemus Kessler, 1872 inhabits the rivers of Southern and possibly Central Kazakhstan. In the studied sample, the fish had a typical minnow shape and body color. The body is oval in cross section, slightly flattened on the abdominal side. The general background of the color is gray-brown, darker on the back, the color lightens towards the belly, along the sides of the body on each side there are 9-12 black spots. In some individuals, the spots merge into a stripe. A dark stripe runs from the eye to the snout. Based on the analysis, we did not reveal significant differences between the minnow from the Beyittibulak River and the previously described samples of Siberian minnow from the Ob River basin. A sample of minnows from the Beyittibulak river is represented by fish of different ages and sizes, so the conditions of existence are quite satisfactory for all stages of life of this fish species.